A huge retroperitoneal mass histologically diagnosed as well differentiated liposarcoma-a case report - Rahman, Md Tahminur; Khan, Abdul Kader; Ferdousi, Shamima; Bela, Shamsun Nahar (Bangladesh Journal of Pathology, 2009)
A 45 year old female presented with huge abdominal swelling (subsequently diagnosed as a retroperitoneal mass (12kg) by ultrasonogram and CT scan), gradual weight loss and respiratory distress for last one year. She had also complaints of anorexia, epigastric pain, and hiccough for one year. Her retroperitoneal mass was resected and sent for histopathological examination which was later diagnosed as well differentiated liposarcoma. Key words: Liposarcoma, retroperitoneal mass doi: 10.3329/bjpath.v24i1.2878 Bangladesh J Pathol 24 (1) : 21-24